Maintenance and practical work for air-conditioning system at Ixora Hotel / Nurul Nabila Azhar - Azhar, Nurul Nabila (Universiti Teknologi MARA UiTM,Perak, 2022)
This report is done due to the training programme that has been provide for students in their final year as competing their bachelor degree. It is one of the great way to train and expose students to the realities of working environment. Through this program, students also can applied all the knowledge, skills and techniques that has been learn from the previous semester which can help them in improving company profile and also their capabilities during practical semester. Practical training is also a requirement in completing all courses taken in order to graduate from university. The students will be allocated with a total of 16 weeks of training period by choosing their own practical place. There are no restriction in choosing their training place such as government or private company as long as that company are performing either building control, facilities management and maintenance, building conservation and heritage, building work and appraisal, development and construction or risk management.